Investigating analgesic and psychological factors associated with risk of postpartum depression development: a case–control study - Suhitharan T; Pham TPT; Chen H; Assam PN; Sultana R; Han NR; Tan E; Sng BL (Neuropsychiatric Disease and Treatment)
Thangavelautham Suhitharan,1 Thi Phuong Tu Pham,2 Helen Chen,2,3 Pryseley Nkouibert Assam,4 Rehena Sultana,2 Nian-Lin Reena Han,5 Ene-Choo Tan,6,7 Ban Leong Sng1,2 1Department of Women’s Anaesthesia, KK Women’s and Children’s Hospital, 2Duke-NUS Medical School, 3Women’s Service, Department of Psychological Medicine, KK Women’s and Children’s Hospital, 4Singapore Clinical Research Institute, 5Division of Clinical Support Services, 6Research Laboratory, KK Women’s and Children’s Hospital, 7SingHealth Paediatrics Academic Clinical Programme, Duke-NUS Medical School, Singapore Aim: The aim of this study was to investigate the role of peripartum analgesic and psychological factors that may be related to postpartum depression (PPD).Methods: This case–control study was conducted in pregnant females who delivered at KK Women’s and Children’s Hospital from November 2010 to October 2013 and had postpartum psychological assessment. Demographic, medical, and postpartum psychological status assessments, intrapartum data including method of induction of labor, mode of labor analgesia, duration of first and second stages of labor, mode of delivery, and pain intensity on hospital admission and after delivery were collected. PPD was assessed using the Edinburgh Postnatal Depression Scale and clinical assessment by the psychiatrist.Results: There were 62 cases of PPD and 417 controls after childbirth within 4–8 weeks. The odds of PPD was significantly lower (33 of 329 [10.0%]) in females who received epidural analgesia for labor compared with those who chose nonepidural analgesia (29 of 150 [19.3%]) ([odds ratio] 0.47 (0.27–0.8), P=0.0078). The multivariate analysis showed that absence of labor epidural analgesia, increasing age, family history of depression, history of depression, and previous history of PPD were independent risk factors for development of PPD.Conclusion: The absence of labor epidural analgesia remained as an independent risk factor for development of PPD when adjusted for psychiatric predictors of PPD such as history of depression or PPD and family history of depression. Keywords: epidural analgesia, childbirth, Edinburgh Postnatal Depression Scale